2018
DOI: 10.1021/acsami.8b15112
|View full text |Cite
|
Sign up to set email alerts
|

Restricting Molecular Mobility in Polymer Nanocomposites with Self-Assembling Low-Molecular-Weight Gel Additives

Abstract: Multiscale investigation of molecular gel additives in polymer matrices guides understanding of how solution-state assemblies result in mechanically enhanced, solid-state nanocomposites. Model polymers, poly­(ethylene oxide-co-epichlorohydrin) (EO–EPI) and poly­(vinyl acetate) (PVAc), were utilized as matrices and reinforced by cholesterol–pyridine (CP) nanofiber networks. The CP nanofillers suppress ethylene oxide segment melting for EO–EPI composites, whereas for PVAc nanocomposites, cause a polymer–gel diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We assume that the increased number of physical bonds ( e.g. , hydrogen bonds between ether bonds or terminated hydroxyl in mPEG-(OH) 1 and hydroxyl groups in peptide hydrogelators) between mPEG-(OH) 1 molecules and peptide hydrogelators leads to the sharp decrease of the CGC for mPEG-(OH) 1 samples with nearly no entanglements . As for entangled mPEG-(OH) 1 samples, the increased number of entanglements may dominate the change of CGC .…”
Section: Resultsmentioning
confidence: 99%
“…We assume that the increased number of physical bonds ( e.g. , hydrogen bonds between ether bonds or terminated hydroxyl in mPEG-(OH) 1 and hydroxyl groups in peptide hydrogelators) between mPEG-(OH) 1 molecules and peptide hydrogelators leads to the sharp decrease of the CGC for mPEG-(OH) 1 samples with nearly no entanglements . As for entangled mPEG-(OH) 1 samples, the increased number of entanglements may dominate the change of CGC .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ideally, a careful combination of these two kinds of soft materials could enhance their advantages and moderate their weaknesses. In fact, several groups have shown that polymer additives may influence critical gelation concentration, gelation time, mechanical properties, or even biological activity of LMWGs [7–17] . In this field, different strategies can be used to combine LMWG and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several groups have shown that polymer additives may influence critical gelation concentration, gelation time, mechanical properties, or even biological activity of LMWGs. [7][8][9][10][11][12][13][14][15][16][17] In this field, different strategies can be used to combine LMWG and polymers. One of them consists of preparing interpenetrating networks (IPNs) in which a second network is formed through the voids of a preformed first network.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic amide [29] or urea-coupled cyclohexane [30], peptides [31][32][33][34], and sugar-based derivatives with distinct helical structures [35][36][37] are typical examples of the former [38][39][40][41][42]. In contrast, cholesterol derivatives that aggregate due to crown moieties, π-π stacking, van der Waals forces, and/or solvophobic properties are a common example of the latter [43][44][45]. Among them, an intermolecular hydrogen-bonding interaction was utilized to prepare helical supramolecular gels.…”
Section: Introductionmentioning
confidence: 99%